Faktor yang Mempengaruhi Pengelolaan Usaha Jamu dan Rempah di Bangkalan - Putra, Rico Salasa; Ismail, Iriani (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Jamu is an Indonesian cultural heritage that has been used since prehistoric times to maintain health, increase body resistance, and prevent and treat disease. Apart from being a medicine, herbal medicine is also useful for preventing disease recurrence and supporting beauty, especially for women. This research uses a qualitative method with a descriptive analytical approach. The aim is to develop the concept of sensitivity to problems, explain the reality related to developing theory from below (grounded theory), and deepen understanding of the phenomena that occur. The research results show that herbal medicine businesses, especially those in the Small and Medium Industry (IKM) sector, experienced a decline in sales from 2019 to 2022. This decline was caused by the transition from traditional to modern organizational models, which had an impact on obstacles in the production process, both in terms of time , energy and costs. To support business continuity, it is recommended that the government provide laboratory testing facilities to ensure product safety and facilitate the processing of "Halal" and "BPOM" certification. This step is expected to increase consumer confidence and help business actors overcome existing challenges.